PENGARUH MODAL KERJA, SOLVABILITAS, DAN LIKUIDITAS TERHADAP PROFITABILITAS PADA PT. SEMEN INDONESIA (PERSERO) TBK - M, Muhaidir Ikram; Sahabuddin, Romansyah; Ali, Ahmad (DECISION : Jurnal Ekonomi dan Bisnis, 2022)
This study has a purpose, namely to test whether the independent variable (X) in this study, namely Working Capital (WCTO), Solvability (DAR), and Liquidity (CR) has an effect on Profitability (ROA) at PT. Semen Indonesia (Persero) Tbk. The population and sample in this study were all data on the financial statements of PT. Semen Indonesia (Persero) Tbk for the 2013-2020 period in each quarter of the research period. Documentation is a data collection technique used in this study. The collected data were analyzed using financial ratios, then entered into multiple linear regression equations. The findings in this study indicate that partially working capital turnover (WCTO), solvability (DAR), and liquidity (CR) have a positive and significant effect on profitability (ROA). That is, every time there is an increase in WCTO, DAR, and CR, it will increase ROA and contrarily. In addition, based on the F-test shows that simultaneously the variables WCTO, DAR, and CR have a positive and significant effect on ROA. Both hypotheses in this study were accepted.